Penyuluhan Terapi Cuci Hidung Pada Pasien di Poliklinik THT RSUD Praya - Yuliyani, Eka Arie; Ika Prasetyaningrum; Silmi Chairan Andi; Muhammad Ibnu Annafi; Muhammad Akbar Hanardi (Universitas Mataram, 2024)
As the sense of smell, the nose has a very important role and is very susceptible to disease. Various pollutants, viruses and bacteria enter with respiratory air through the nasal cavity. So physiological changes in the nasal cavity can cause many problems in the sinonasal area. To maintain the cleanliness of the nasal cavity, efforts need to be made in the form of nasal washing therapy which is considered practical, easy, cheap and painless for the user. The aim of this health education is to provide information and knowledge to the public about the importance of nasal washing therapy and how to do it properly and correctly. In this activity, the counseling participants were very enthusiastic about the material presented by ENT Specialist Doctors and Young Doctors from FK Unram at Praya Regional Hospital, by holding quite interesting question and answer discussions. Apart from that, the participants also dared to try doing nose washing therapy after being given an example by the Young Doctors through a nose washing demonstration. The results of this activity can be used as evaluation and improvement for carrying out similar activities in the future